Characterization of the Gut Microbiome in Healthy Dogs and Dogs with Diabetes Mellitus - Tsz Ching Kwong; Eddie Chung Ting Chau; Mark Chi Ho Mak; Chi Tung Choy; Lee Tung Chan; Chun Keung Pang; Junwei Zhou; Phoebe Hoi Ching Poon; Yuqiong Guan; Stephen Kwok Wing Tsui; Shun Wan Chan; George Pak Heng Leung; et al. (Animals, 2023)
With a close pathogenetic resemblance to human diabetes, canine Diabetes Mellitus, a chronic metabolic disease featuring abnormally high blood sugar levels, is increasing in prevalence worldwide. Unlike humans, canine glycemic control requires life-long insulin injections and dietary control in most cases, thereby jeopardizing diabetic dogs’ quality of life and increasing the difficulty of disease control. While many research studies have focused on elucidating the relationship between the canine gut microbiome and diseases, there is currently no research on the subject of diabetes mellitus in dogs. We hypothesized that the gut microbiome of canines with diabetes mellitus is different from that of healthy controls. Thus, we performed targeted 16S rRNA sequencing and comprehensive bioinformatic analysis to compare the gut microbiome profiles of 16 diabetic dogs with those of 32 healthy dogs. Clostridioides difficile, Phocaeicola plebeius, Lacrimispora indolis, and Butyricicoccus pullicaecorum were found to be enriched in diabetic dogs. A distinct shift towards carbohydrate degradation metabolic pathways was found to be differentially abundant in the diabetic subjects. Alteration of the co-occurrence network was also evident in the diabetic group. In conclusion, our study suggests that the gut microbial landscape differs in diabetic canines at the genera, species, functional, and network levels. These findings have significant implications for disease management, and thus warrant further research.